Drug-related problems in elderly patients with AECOPD and pharmaceutical intervention practice: a prospective study - Ma, Zengqing; Shi, Hongjun; Hong, Guojun; Wu, Lianping; Lin, Yu (Frontiers in Pharmacology, 2025)
BackgroundElderly patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) face an elevated risk of drug-related problems (DRPs) owing to age-related decline in physiological reserve and multiple comorbidities. This study aims to systematically identify and categorize the DRPs of elderly patients with AECOPD, analyze their causes and risk factors, and evaluate the impact of pharmaceutical interventions on resolving DRPs.MethodsElderly patients hospitalized with AECOPD at Gaochun Hospital Affiliated to Jiangsu University were enrolled in this prospective study from 1 January 2023 to 31 December 2024. Clinical pharmacists classified and documented DRPs using the Pharmaceutical Care Network Europe (PCNE) V9.1 Classification System, followed by targeted pharmaceutical interventions based on causes of DRPs.ResultsA total of 544 AECOPD patients were included in the study. Among them, 393 DRPs were identified in 300 patients, resulting in an occurrence rate of 55.15%. “P2 Treatment safety” was the major DRPs (n = 177, 45.04%). Univariate and multivariate analysis showed that the number of drugs >15 (OR: 136.648, 95% CI: 38.693–482.583) and the number of comorbidities >2 (OR: 161.092, 95% CI: 43.880–591.402) were the risk factors for DRPs (P < 0.001). 472 causes were analyzed by clinical pharmacists. “C9.1 No or inappropriate outcome monitoring (including TDM)” was the most common cause of DRPs (n = 163, 34.53%). Clinical pharmacists proposed 435 interventions to address DRPs, of which 398 (91.49%) interventions were accepted. In the end, 294 (74.81%) DRPs were totally solved, and 18 (4.58%) DRPs were partially solved.ConclusionThe incidence of DRPs is high in elderly hospitalized patients with AECOPD in China. The number of comorbidities and prescription drugs are important predictors for DRPs. The active involvement of clinical pharmacists in the management of AECOPD patients can enhance both the safe and effective use of medications among elderly patients, as well as the overall quality of pharmaceutical care.